Surface settlement in saturated loess stratum during shield construction: Numerical modeling and sensitivity analysis. (January 2022) - Zhu, Caihui; Wang, Songhe; Peng, Sen; Song, Yili
Highlights: Soil parameters of saturated Q3 loess are totally different from saturated soft soil. Mohr-Coulomb model can better simulate saturated loess than Soft Soil model. Grouting and eccentric effect of shield are more sensitive to surface settlement. Lower limit of grout filling ratio and upper limit of eccentric ratio is 60% and 0.5%. Bottom leakage of lining has the greater influenced on surface settlement trough. Abstract: During shield construction of Xi'an metro, saturated loess stratum with loose soil structure and poor engineering properties is often encountered, which is prone to cause excessive surface settlement (SS) and risk to the safety of upper infrastructures. Six factors that affect SS during shield construction and post-construction stages in Xi'an metro were focused, including shield tail grouting pressure ratio δ, eccentric over-excavation ratio α, groundwater decline, shield earth chamber pressure λ, shield tail grout filling ratio ξ, and leakage position of lining. According to Peck's formula, two characteristic parameters of SS were defined, i.e., maximum surface settlement (MSS) and settlement trough width (STW). Based on the Biot's theory, the computation of fluid–solid coupling during shield construction in saturated loess stratum was realized. Local sensitivity analysis indicates that SS of saturated loess stratum is more sensitive to shield tail grout filling ratio, eccentric over-excavation ratio, groundwater decline and grouting pressure ratio. In order to reduce the SS and its influence range, the following standards should be satisfied, i.e., ξ > 60%, α ≤ 0.5%, 1.0 ≤ δ ≤ 1.1 and 0.9 ≤ λ < 1.6. Moreover, in the post-construction stage, the closer the leakage position to the bottom of the tunnel, the greater the induced MSS and the wider the STW, and waterproofing measures for the lining near the bottom plate should be taken to ensure that the relative permeability coefficient of the lining β ≤ 0.001. The groundwater level should also be maintained in the overlying stratum.